2019
DOI: 10.1111/all.13784
|View full text |Cite
|
Sign up to set email alerts
|

Benzo(a)pyrene facilitates dermatophagoides group 1 (Der f 1)‐induced epithelial cytokine release through aryl hydrocarbon receptor in asthma

Abstract: Background Environmental pollutants, which coexist with allergens, have been associated with the exacerbation of asthma. However, the underlying molecular mechanisms remain elusive. We sought to determine whether benzo(a)pyrene (BaP) co‐exposure with dermatophagoides group 1 allergen (Der f 1) can potentiate Der f 1‐induced asthma and its underlying mechanisms. Methods The effect of BaP was investigated in Der f 1‐induced mouse model of asthma, including airway hyper‐responsiveness, allergic inflammation, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
58
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(68 citation statements)
references
References 81 publications
(107 reference statements)
6
58
0
Order By: Relevance
“…[9][10][11] Xu et al 7,8 reported that ambient ultrafine particles could promote differentiation of T H 17 and T H 2 cells in a Jagged 1/Notch 4-dependent manner. Also, Wang et al 13 reported that the PM-associated PAH BaP facilitates Der f 1-induced epithelial thymic stromal lymphopoietin and IL-33 release through the AhR-reactive oxygen species axis and enhances lung inflammation. Quintana et al 5 reported that the AhR in T cells can regulate the balance of T H 17/Treg cells in a ligand-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11] Xu et al 7,8 reported that ambient ultrafine particles could promote differentiation of T H 17 and T H 2 cells in a Jagged 1/Notch 4-dependent manner. Also, Wang et al 13 reported that the PM-associated PAH BaP facilitates Der f 1-induced epithelial thymic stromal lymphopoietin and IL-33 release through the AhR-reactive oxygen species axis and enhances lung inflammation. Quintana et al 5 reported that the AhR in T cells can regulate the balance of T H 17/Treg cells in a ligand-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…It is expressed universally in multiple cell types: mast cells, macrophages, dendritic cells, T cells, and epithelial cells. [5][6][7][8][9][10][11][12][13] Particulate matter of 2.5 mm or less in diameter (PM2.5) is very small and can enter the airways and reach the alveoli. These small PM sizes are partly eliminated by alveolar macrophages, but some of them (especially those of <1 mm in diameter [like ultrafine particles]) pass into the blood circulation.…”
mentioning
confidence: 99%
“…The responders of IL‐25 are numerous as well, including epithelial cells themselves, TSLP‐DC (dendritic cells activated by TSLP)–activated memory Th2 cells, IL‐9–producing Th9 cells, airway smooth muscle (ASM) cells, endothelial cells, eosinophils, basophils, and type 2 innate lymphoid cells (ILC2s, a population of non‐B/non‐T cells capable of producing Th2 cytokines), on which the heterodimer receptors of IL‐25, namely IL‐17RA/IL‐17RB, are expressed 39‐41 …”
Section: Epithelium‐derived Il‐25mentioning
confidence: 99%
“…BaP-induced activation of AhR and the development of immune disorders, such as allergies and autoimmune diseases (Schulz, Smit, & Pieters, 2013;Wang et al, 2019). However, the direct relationship between immune disorders and BaP-induced AhR activation is still poorly understood.…”
mentioning
confidence: 99%